Gold nanoparticles associated with temozolomide for glioblastoma Multiforme Treatment - Gialluca, Vanessa Dias (2021)
Malignant neoplasms represents a group of diseases that features, as a characteristic, the genetic differentiation of the original tissue, leading to the disordered growth of cells, invading normal tissues and organs. Among the most aggressive tumors, Glioblastoma Multiforme has a mortality rate around 95% and survival’s average of 15 months, even though all treatment available. Temozolomide (TMZ) is the chemotherapeutic drug so far tested and approved with the highest response in this tumor sub-type and must be associated to other treatments to achieve better results. Thus, the purpose of this work was to evaluate the performance of this therapeutic modality with gold nanoparticles (AuNPs) and also combined with radiotherapy. TMZ hydrolysis was characterized at different pH and the chemical changes on molecular structure was determined via Fourier Transform Infrared Spectroscopy (FT-IR). The treatment performance was verified in vitro test using TMZ, TMZ plus AuNPs and associated with radiotherapy. The TMZ concentrations were varied from 0 (control group) to 1000µM, combined with AuNPs from 0 (control group) to10¹⁰ nanoparticles per well. The results showed the drug is stable at pH values between 2 to 4, but for pH values close to the physiological or basic medium, degradation is accentuated reaching a rate of 16 %/hour. The changes on molecular structure of TMZ can be observed through the FT-IR spectra, where the release of oxygen in the structure has influence on C=O group. The results of in vitro experiments showed that the highest poor results in the absence of ionizing irradiation. However, for experiments with TMZ and nanoparticles associated to radiotherapy, the performance of the treatment increased. In summary, the AuNPs showed important results under irradiation, revealing the same level of cytotoxicity for the highest TMZ concentration without irradiation. Also, the synergic effect between AuNPs and TMZ was observed under irradiation condition.